A case of familial transmission of community-acquired methicillin-resistant Staphylococcus aureus carrying the lnu(A) gene in Santa Fe city, Argentina - Méndez, Emilce de los A. (2012)
Fil: Mendez, Emilce de los A. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas; Argentina.